(untitled) (Journal of Fatima Jinnah Medical University, 2024)
Background: Emotional intelligence (EI) is associated with the success of healthcare professionals. Mental health, physical health, academic performance, and stress management are all linked to high EI. The academic achievement relies on one’s social skills and emotional stability. This study aimed to determine the correlation between emotional intelligence scores and academic performance in medical undergraduates. Subjects and methods: A cross-sectional study was conducted among second to final-year MBBS students at Nishtar Medical University (NMU). A total of 302 medical students were divided into two groups including 145 males and 157 females. Academic performance was assessed by using the last professional examination percentage and Emotional Intelligence (EI) was calculated by the Emotional Intelligence Scale [EIS] (comprising ten components: self-awareness, empathy, self-motivation, emotional stability, managing relations, integrity, self-development, commitment, value orientation, and altruistic behaviour). The data was analyzed using SPSS version 26. The overall EIS score was correlated with Academic performance using Spearman’s correlation test. Results: Among a total of 302 medical students, 145 (48%) were male and 157 (52%) were female with a mean (SD) of age 21.8 ± 1.396. A significant correlation was identified between overall EI and academic scores (r=0.204, p-value = 0.000) of medical students. The academic score of female students showed a significant correlation with all components of EIS (p-value = 0.000) while the academic score of male students was only correlated with one component of EIS [emotional stability] (p=0.049). Conclusion: This study highlights the significant correlation among EI and academic performance, and suggests that EI needs to be integrated with academic practices and culture. Thus, more attention should be given to the development of EI in medical students to improve their academic performance, clinical skills, emotional stability, and stress management.